Enhancing Critical Thinking: Leveraging Blended Learning and Higher Order Thinking Skills - Murcahyanto, Hary (Indonesian Journal of Advanced Research, 2025)
This study aims to determine the influence of blended learning on students' critical thinking skills. This research utilizes a quantitative approach with a quasi-experimental design, employing a time series method.The research sample used a class drawing technique consisting of two classes with a sample of 30 students. The tools employed included essay questions and questionnaires to assess critical thinking variables and blended learning through the HOTS approach, in addition to field notes. The findings of the study indicate that implementing the blended learning model combined with the HOTS approach enhances students' critical thinking abilities. This is evidenced by the results of the anova test obtained an anova value of F calculated as 5.851 with a significance level of 0.036. The hypothesis is accepted since the calculated F value exceeds the F table value. Based on the study’s findings, it can be concluded that implementing the blended learning model with the HOTS approach is effective in enhancing students' critical thinking abilities in employment-related topics.